Urban food systems as vehicles for sustainability transitions - Olsson, E. Gunilla Almered (Bulletin of Geography. Socio-economic Series, 2018)
Strategies and action plans for sustainable food provisioning and urban food security are in progress in many urban regions both in the global North and South. A number of urgent challenges need to be confronted such as increasing uncertainty and unpredictability related to stronger dependence on a global market for food import, ongoing political unrest and environmental conflicts, increasing resource scarcity and climate warming making food production hazardous. There is an increased vulnerability with respect to food security for human societies, both in developing and developed countries. The food security dimension of access to healthy food is related to equality and poverty and is relevant for cities in the North via the segregation challenges. The food system issue is well-suited for assessing sustainable development since food provisioning is both a multiscale and cross-sectorial issue and thus addresses more than the three dimensions of social, economic and environmental sustainability. How is the planning for sustainable food strategies in urban regions in Europe concordant with the United Nations Global Sustainable Development Goals and with the transition towards sustainable futures? This paper deliberates on using the food system issues for sustainability transition, drawing on the forthcoming 2018 IPBES (Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services) work on pathways for sustainable futures and a recent survey of existing urban food system strategies. Against this background, some reflections are given relevant for the ongoing work on a local urban food strategy for the city of Gothenburg, Sweden.